Pemanfaatan Media Sosial Youtube dan Tiktok Sebagai Alternatif Edukasi Keamanan Pangan - Mellia Harumi; Inneke Hantoro; Budi Widianarko; Bernadeta Soedarini (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2022)
Food safety is one aspect of quality that is a necessity. Therefore, food safety needs to be well understood by all levels of society. Information related to food safety can be easily obtained in today's digital era through various social media. This ease of access needs to be balanced with the delivery of precise and accurate information. Attractive visualization as an illustration in educational design can increase new knowledge for the community. Youtube and Tiktok were chosen as educational media for delivering information related to food safety through the Community Service program. The education delivered on Youtube includes 2 types of information, namely the method of discussing the latest news and food safety in the form of courses at the Faculty of Agricultural Technology, Soegijapranata Unika. Short videos and animations related to microplastics and food safety were delivered through Unika’s Food Tech Tiktok social media, targeting teenagers as the audience. Through this Community Service activity, public would get the reliable education or information about food safety from online media easily. Youtube and Tiktok viewers can also share important messages contained in the video to other social media accounts.